2016
DOI: 10.1080/09603123.2016.1194384
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional survey of environmental health in remote Aboriginal communities in Western Australia

Abstract: Poor environmental health is prevalent in remote Aboriginal communities and requires further delineation to inform environmental health policy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 24 publications
1
42
0
3
Order By: Relevance
“…This is problematic because of the few studies that have, Indigenous people have been found to be more susceptible to respiratory and ischaemic heart disease from, for example, exposure to PM 2.5 , Hanigan et al 2008. Sources of air pollution in rural areas, particularly natural sources such as bush fires and dust storms, may inequitably affect Indigenous communities, compounding their health burden from air pollution exposure (Knibbs and Sly 2014, Masterman-Smith et al 2016, Melody et al 2016. Our changing climate may serve as an additional factor in exacerbating these health burdens on Indigenous Australians, as well as intensifying emissions from natural sources in rural areas (Webb et al 2014.…”
Section: Introductionmentioning
confidence: 99%
“…This is problematic because of the few studies that have, Indigenous people have been found to be more susceptible to respiratory and ischaemic heart disease from, for example, exposure to PM 2.5 , Hanigan et al 2008. Sources of air pollution in rural areas, particularly natural sources such as bush fires and dust storms, may inequitably affect Indigenous communities, compounding their health burden from air pollution exposure (Knibbs and Sly 2014, Masterman-Smith et al 2016, Melody et al 2016. Our changing climate may serve as an additional factor in exacerbating these health burdens on Indigenous Australians, as well as intensifying emissions from natural sources in rural areas (Webb et al 2014.…”
Section: Introductionmentioning
confidence: 99%
“…2 A large burden of skin disease in Indigenous Australians has been reported, but mainly in children; [20][21][22] we found that the negative impact of skin infections extends into adulthood. Indigenous communities with housing problems and overcrowding as environmental risk factors are more likely to report skin conditions as health problems, 23 and streptococcal skin infections are associated with acute post-infectious glomerulonephritis and CKD. 24 The association between infections and AKI in our study reinforces the importance of addressing the underlying environmental and economic determinants of health, and of reducing barriers to identifying and treating infections in a timely manner.…”
Section: Discussionmentioning
confidence: 99%
“…gedrängten Wohnverhältnissen lebten [20]. Ähnliche Ergebnisse liegen für das Infektionsrisiko mit akuten Atemwegserkrankungen auch aus anderen westlichen Ländern vor [21,22]. Gedrängte Wohnverhältnisse könnten also möglicherweise auch ein Risikofaktor für eine SARS-CoV-2-Infektion sein, wie erste Berichte aus den USA und Großbritannien vermuten lassen [23,24].…”
Section: Soziale Ungleichheit Und Covid-19-risikofaktorenunclassified